A proposal of drain removal criteria in hepatobiliary resection. (24th June 2022) - Watanabe, Nobuyuki; Mizuno, Takashi; Yamaguchi, Junpei; Yokoyama, Yukihiro; Igami, Tsuyoshi; Onoe, Shunsuke; Uehara, Kay; Sunagawa, Masaki; Ebata, Tomoki
Abstract: Background: Standardized criteria for drain removal in hepatobiliary resection are lacking. Here, we evaluated the outcomes of delayed removal policy in this extended surgery. Methods: Patients undergoing hepatectomy with biliary reconstruction between 2012 and 2018 were retrospectively reviewed. The drains were removed on postoperative day (POD) 7 when the drainage fluid was grossly serous, biochemically normal, and negative for bacterial contamination as assessed by Gram staining; additionally, no abnormal fluid collection was confirmed by computed tomography. Clinically relevant abdominal complications (CRACs), including biliary leakage, pancreatic fistula or intra‐abdominal abscess, served as the primary outcome measure. Results: Among 374 study patients, surgical drains were removed in 166 (44.3%) patients who met the criteria. Of these patients, 16 (9.6%) patients subsequently required additional drainage due to CRAC. Drains were retained and exchanged in 208 (55.6%) patients who did not meet the criteria. Of these, exchanged drains were soon removed in 34 patients due to no signs of CRAC. The diagnostic ability of the criteria revealed 0.916 sensitivity, 0.815 specificity, and 0.866 accuracy. Conclusion: The four findings on POD 7 worked well as criteria for drain removal, and these criteria may be helpful in drain management after hepatobiliary resection. Abstract : Watanabe and colleagues report on the safety of institutional drain management after hepatobiliary resection. The Nagoya rule composed of four clinical findings on postoperative day 7 showed high sensitivity and specificity as a guide for drain removal. The delayed and cautious drain removal strategy was safe after complex hepatobiliary resection.